Pengaruh Model Pembelajaran Kooperatif Terhadap Peningkatan Mutu Hasil Belajar Siswa SMPN 13 Bekasi - Mumtaaz Tsumu, Damara; Islami, Tasya Bilkis; Jadid, Khalis; Haryono, Pauzan (Program Studi Pendidikan Agama Islam, Sekolah Pascasarjana Universitas Islam 45, 2024)
The purpose of the research was to determine the effect of cooperative learning models consisting of cognitive, affective and psychomotor on improving the quality of learning outcomes of SMPN 13 Bekasi students. The research method uses quantitative with the experimental type of pre-test, post test, non-equivalent control group design with primary data sources derived from the results of interviews and student observations, while secondary comes from journals, books, documents that support the results of research with data analysis using descriptive statistics and partial tests. The results showed that the cooperative learning model through the group investigation method had no effect on cognitive, affective and psychomotor learning outcomes in SMPN 13 Bekasi students which could be caused by less than optimal implementation, different student abilities, unsupportive group dynamics, minimal interaction between students or groups not functioning properly, this could result in stagnant learning outcomes and external variables that were not taken into account.